Diffusion-Weighted Imaging Lesions After Intracerebral Hemorrhage and Risk of Stroke: A MISTIE III and ATACH-2 Analysis. Issue 2 (February 2021) - Murthy, Santosh B.; Zhang, Cenai; Gupta, Ajay; Cho, Sung-Min; Rivera-Lara, Lucia; Avadhani, Radhika; Gruber, Joshua; Iadecola, Costantino; Falcone, Guido J.; Sheth, Kevin N.; Qureshi, Adnan I.; Goldstein, Joshua N.; et al.
Abstract : Background and Purpose: Punctate ischemic lesions noted on diffusion-weighted imaging (DWI) are associated with poor functional outcomes after intracerebral hemorrhage (ICH). Whether these lesions increase long-term risk of stroke is poorly understood. Methods: We pooled individual patient data from the ATACH-2 trial (Antihypertensive Treatment of Acute Cerebral Hemorrhage) and the MISTIE III trial (Minimally Invasive Surgery Plus Alteplase for Intracerebral Hemorrhage Evacuation Phase 3). We included subjects with a magnetic resonance imaging scan. The exposure was a DWI lesion. The primary outcome was any stroke, defined as a composite of ischemic stroke or recurrent ICH, whereas secondary outcomes were incident ischemic stroke and recurrent ICH. Using multivariate Cox regression analysis, we evaluated the risk of stroke. Results: Of 505 patients with ICH with magnetic resonance imaging, 466 were included. DWI lesions were noted in 214 (45.9%) subjects, and 34 incident strokes (20 ischemic stroke and 14 recurrent ICH) were observed during a median follow-up of 324 days (interquartile range, 91–374). Presence of a DWI lesion was associated with a 6.9% (95% CI, 2.2–11.6) absolute increase in risk of all stroke (hazard ratio, 2.6 [95% CI, 1.2–5.7]). Covariate adjustment with Cox regression models also demonstrated this increased risk. In the secondary analyses, there was an increased risk of ischemic stroke (hazard ratio, 3.5 [95% CI, 1.1–11.0]) but not recurrent ICH (hazard ratio, 1.7 [95% CI, 0.6–5.1]). Conclusions: In a heterogeneous cohort of patients with ICH, presence of a DWI lesion was associated with a 2.5-fold heightened risk of stroke among ICH survivors. This elevated risk persisted for ischemic stroke but not for recurrent ICH. Abstract : Supplemental Digital Content is available in the text.